Novedades florísticas para la Sierra de Gádor (Almería, España) - Giménez Luque, Esther; Gómez Mercado, Francisco (Lazaroa, 2001)
We comment on twelve taxa of floristic and chorological interest collected in the Gádor Mountains (Almería). All of them are new records for the Alpujarra-Gador sector. We highlight the new records for Serratula baetica subsp. baetica and Potentilla reuteri in Almería province.